Analisis Sektor Potensial dan Kesempatan Kerja Sektoral di Kabupaten Buleleng - Dharma Putra, Dede Satrya; Kartika, Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
GDP growth rate and the amount of the value of GDP Buleleng high anyway it did not reflect the magnitude of the growth of GDP per capita Buleleng. The condition is exacerbated by high rates of unemployment and poverty in Buleleng, so the potential sectors need to be developed to help overcome these problems. Purpose of this study was to determine the potential sectors and sectoral employment in Buleleng.The study used secondary data in the form of contributions and the rate of growth of GDP at constant prices, the labor force works, population, distance between districts or cities in the province of Bali. Collecting data through non-participant observation and documentation. The analysis technique used LQ, MRP, Overlay, Gravity Analysis, Share Esteban Marquillas Shift, Shift Share, multiplier Base ratio.The results showed a potential sector is the agricultural sector. The linkage of the most powerful in Buleleng Regency is the city of Denpasar. Sectors that have competitive competitiveness and specialization is the agricultural sector. Job opportunities in Buleleng positively influenced by the growth of employment in the province of Bali, but not for a mix of industrial and competitive advantage. Job opportunities in the sector of the base have a positive impact on the increase in total employment and non-employment sector basis.The government must improve infrastructure or infrastructure for agriculture. The Government may also establish cooperation with other regions to make Buleleng as agropolitan so as to help improve the welfare and employment.
Keywords: potential sectors; sectoral employment